Športna dejavnost dijakov Srednje zdravstvene šole Ljubljana - Bon, Marta (Šport (Ljubljana), 2019)
Apart from positive effects on health, sports activity also affects academic achievement, motoric, personality and social development of children and adolescents. However, the positive effects can only be achieved through sufficient frequency and intensity of sports activity. The aim of our study was to examine the level of sports activity in students of the Secondary School of Nursing Ljubljana and determine differences according to gender, year of study and academic achievement in relation to their engagement in sport. 269 students (30,4 %) agreed to participate in the survey, 206 were women and 63 men, aged between 16 and 18 (75,46 %). The majority of students were physically active at least two to three times a week (44.96 %), while no significant difference between genders (p=0,159), study years (p=0,753) in physical activity was obtained. Furthermore, there was also a tendency towards significance comparing different academic achievement in physical activity frequency (p=0,056). The results suggest regular sports activity of the students, although less then recommended by the WHO. It can also be postulated that higher levels of sports activity are associated with better academic achievement. In conclusion, students of the Secondary School of Nursing Ljubljana must be advised to increase their weekly physical activity levels.
Keywords: adolescents; healthy lifestyle; leisure time; mladostniki; prosti čas; Secondary School of Nursing Ljubljana; sport; sports activity; Srednja zdravstvena šola Ljubljana; šport; športna aktivnost; zdrav življenjski slog